Alcohol consumption by university students. Study of the relationships between of the causes and negative effects - Méndez Garrido, Juan Manuel; Azaustre Lorenzo, María del Carmen (Revista Complutense de Educación, 2016)
This research analyzed the main reasons that led to alcohol consumption in students of the University of Huelva. The aim was to understand the causes, the negative effects and the relationship between the factors of alcohol consumption. A descriptive, cross-sectional methodology was followed, using an ad hoc questionnaire as data collection instrument. 1.165 students enrolled in the University of Huelva during the year 2012/2013 participated in the study. The sampling was stratified and within each stratum a simple random process was apllied. Bivariate analysis, correlations, chi-square, variance, means, standard deviations were applied; consumption frequency was evaluated and factorial reduction was made. The most relevant results of the study showed that some variables correlated positively as well as scale factors. The degree of significance and index of reliability of these factors were relatively high. The conclusions indicate that there are no significant differences between the age of consumption and sex, since both sexes begin alcohol consumption between the ages of 16 and 20. The relationship between the variables of course and consumption frequency was the inverse: at lower levels, consumption increases and at higher levels, it decreases. Also, the implementation of preventive measures emerges as necessary to counterbalance alcohol consumption in university students and its negative health effects.
Keywords: Alcohol; consumption; health risk; students; university